Diffusion Barriers in the Squid Nerve Fiber : The axolemma and the Schwann layer - Villegas, Raimundo (The Rockefeller University Press, 1962)
The squid nerve barriers are formed by (a) the axolemma (membrane of the axon proper), a membrane 80 Å thick perforated by cylindrical pores 4.0 to 4.5 Å radius, and (b) the Schwann layer, constituted of numerous cells forming a layer one cell thick, crossed by 60 Å wide slit channels. If a molecule present in the axoplasm has to reach the extraneural space, it has to pass (a) the pores, and (b) the channels, in series, and the diffusion rate will depend on the effective diffusion areas per unit path length, A(pd)/Δx for the axolemma, and A(cd)/Δx for the Schwann layer. By addition, A(nd)/Δx, the transneural effective area for diffusion per unit path length is obtained. The diffusion rates of C(14)-ethylene glycol (2.2 Å radius), and C(14)-glycerol (2.8 Å radius) were measured. The diffusion rate of H(3)-labeled water (1.5 Å radius) has been previously determined. The results expressed in terms of A(nd)/Δx (mean values ± SD, referred to 1 cm(2) of nerve surface) are 5.3 ± 1.4 cm for water, 2.5 ± 0.4 cm for ethylene glycol, and 0.29 ± 0.03 cm for glycerol. Theoretical values for A(nd)/Δx of 2.5 and 0.83 cm for ethylene glycol and glycerol have been calculated. The agreement between the theoretical values for A(nd)/Δx and the experimental ones supports the diffusion barrier model described above.